Topography and structural changes of Anak Krakatau due to the December 2018 catastrophic events - Herlan Darmawan; Bachtiar Wahyu Mutaqin; Wahyudi Wahyudi; Agung Harijoko; Haryo Edi Wibowo; Nia Haerani; Mamay Surmayadi; Syarifudin Syarifudin; Raditya Jati; Suratman Suratman; Wikanti Asriningrum (Indonesian Journal of Geography, 2020)
The flank collapse of Anak Krakatau on 22 December 2018 caused massive topography losses that generated a devastating tsunami in Sunda Strait, which then followed by eruptions that progressively changed the topography and structure of Anak Krakatau. Here, we investigated topography and structural changes due to the December 2018 flank collapse and the following eruptions by using high resolution Digital Elevation Model (DEM) before and after the events and sentinel 1A satellite image post-flank collapsed. Results show that the volumetric losses due to the 22 December 2018 flank collapsed is ~127 x 106 m3, while the following eruptions caused ~0,8 x 106 m3 losses. Structural investigation suggests two structures that may act as failure planes. The first structure is located at the western part of volcanic edifice that associated with hydrothermal alteration and the second failure is an old crater rim which delineated an actively deform volcanic cone.